Strategi Pengembangan Portofolio Produk Investasi Bank ABC - Sampor Ali; Lukman M Baga; Bunasor Sanim (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2017)
This article particularly aimed to analyze the Strengths, Weaknesses, Opportunities and Threats of the investment products. Assessing the environmental factors that affect the attractiveness of the industry and the business Strength of investment product in wealth management division in GE matrix provides recommendations of the alternative strategy for investment products in the future. The formulation of strategies product development was carried out using a portfolio analysis of Matrix General Electric (GE). The GE Matrix showed that the deposit product and retirement savings were in the first quadrant while attraction or interest in the industry was still high. Savings products were in quadrant II Planning, indicating that the company had a high business strength, but the attractiveness of the industry for these categories was in the normal position. The bancassurance products, bonds and mutual funds were in quadrant III where at this phase of the company business Strength was in the normal position, and the attractiveness of the market or industry was also in the normal position. Strategies for the development of deposits and retirement savings products included the market development and product development strategies. Savings Product Planning used penetration and product development whereas the Bancassurance products, bonds and mutual funds used market penetration strategy.Keywords: bank, wealth management, portfolio analysis, GE matrixAbstrak: Penelitian bertujuan melakukan analisa kekuatan, kelemahan, peluang serta ancaman produk investasi. Mengkaji faktor lingkungan yang memengaruhi daya tarik industri dan kekuatan bisnis produk investasi di divisi wealth management dalam bentuk matrik portofolio produk, sehingga dapat memberikan rekomendasi strategi alternatif terhadap produk investasi di masa depan. Rumusan strategi pengembangan portofolio menggunakan Matriks General Electric (GE). Hasil Matriks GE menunjukkan bahwa produk deposito dan tabungan pensiun berada dalam kuadran I, yaitu daya tarik dalam industri masih tinggi. Produk Tabungan Perencanaan berada dalam kuadran II yaitu perusahaan memiliki kekuatan bisnis yang tinggi namun daya tarik industri untuk kategori-kategori tersebut pada posisi biasa. Sedangkan produk bancassurance, obligasi dan Reksadana berada pada kuadran III dimana pada fase ini kekuatan bisnis perusahaan pada posisi biasa dan daya tarik pasar atau industri juga pada posisi biasa. Perumusan strategi pengembangan untuk produk deposito dan tabungan pensiun menggunakan strategi pengembangan pasar dan strategi pengembangan produk. Produk Tabungan Perencanaan menggunakan Penetrasi dan Pengembangan produk. Produk Bancassurance, Obligasi dan Reksadana menggunakan strategi penetrasi pasar.Kata kunci: bank, wealth management, analisis portofolio, matriks ge